Environmental Kuznets curve for the Moroccan economy - Anas, Mossadak (Archives of Business Research, 2017)
The Environmental Kuznets Curve (ECK) analyses the relationship between economic growth and environmental deterioration. The traditional view that that economic development and environmental quality are contradictory objectives reflects a pure scale effect and does not take into account technological developments. the ECK hypothesis suppose that once economies reach a certain level of development (turning point), environmental degradation tends to decline due to the use of more strict application of environmental rules and increasing public awareness of environmental issues The aim of this paper is to estimate an environmental Kuznets curve for the Moroccan economy. The objective is to investigate its existence and calculate its turning point. The empirical findings show that the Moroccan economy would observe a reversal of its CO2 emissions by 2040. At this point of time, the real GDP per capita would reach 7800 dollars.